A case report of a giant appendiceal mucocele and literature review - Mpapho Joseph Motsumi; Pako Motlaleselelo; Gezahen Ayane; Sheikh Omar Sesay; Johamel Ramos Valdes (The Pan African Medical Journal, 2017)

(untitled)
A 43-year-old female presented at the accident and emergency department of Princess Marina Hospital, Gaborone, Botswana. She reported a deep dull aching pain of two years duration in the right iliac fossa that has been progressively becoming worse. Ultrasound revealed a large sausage like cystic mass extending from the pelvis up to the medial aspect of the ascending colon. CT scan showed a large sausage like cystic mass extending from the pelvis up to the hepatic flexure of the colon with the cecum displaced. No metastatic features were seen. We made an impression of appendiceal mucocele. A semi-elective laparotomy was scheduled. Intraoperative findings: a giant intact cystic distended appendix with involved base, displacing the cecum cranially. A right hemicolectomy was performed. The histopathological results revealed a low-grade appendicular mucinous neoplasm with no lymph node involvement. The surgical margins were free. The patient recovered uneventfully.